Car pooling application for university students - Chang, Li Hao (2022)

(untitled)
The concept of car-pooling has been around in the market for a while, and it has become a more practical and cost-effective way to travel nowadays due to the advancement of technology used. This project will present a new mobile application solution for the development of car-pooling applications for university students. The project will provide students with an alternative way to commute during their daily routine. We also hope to share the benefits of carpooling through this project with numerous university students. The special features for this project will be that users need to be verified to use the carpool service, and the admin will review the student ID uploaded and decide which user needs to have a verified account. The application will be developed using the React Native framework, as NPM includes many ready-to-use libraries that enable a faster development process. It will be an online application, which always requires an internet connection to receive or send data to the cloud database. The main delivery platform for this project will be the Android platform, as it has more users and allows more flexibility in application selection. In terms of functionality, the application will provide several main features such as user authentication, managing user profiles, posting ride requests, checking requested rides, and so on. The name of this application will be DinoPool, with a cute app icon to attract user attention at the same time as providing more simplicity on the user interface. The user will be further categorised into two different roles, which are: rider or driver. Both roles will have the same interface but slightly different functionality. A rider can request to ride along on the driver’s route, while the driver can request to pick up the rider at their origin place. The application will provide three carpool services, which are immediate, scheduled, and regular; each service is different in terms of time request and methods. Although single-occupant travel remains popular in Malaysia, we hope to promote the concept of ride sharing to the millennials, who are university students who are already immersed in technology practically and are more comfortable interacting with technology.